Building a Stronger System for Tracking Nutrition-Sensitive Spending: A Methodology and Estimate of Global Spending for Nutrition-Sensitive Foreign Aid. (December 2015) - Ickes, Scott B.; Trichler, Rachel B.; Parks, Bradley C.
Background: There is growing awareness that the necessary solutions for improving nutrition outcomes are multisectorial. As such, investments are increasingly directed toward "nutrition-sensitive" approaches that not only address an underlying or basic determinant of nutrition but also seek to achieve an explicit nutrition goal or outcome. Understanding how and where official development assistance (ODA) for nutrition is invested remains an important but complex challenge, as development projects components vary in their application to nutrition outcomes. Currently, no systematic method exists for tracking nutrition-sensitive ODA. Objective: To develop a methodology for classifying and tracking nutrition-sensitive ODA and to produce estimates of the amount of nutrition-sensitive aid received by countries with a high burden of undernutrition. Methods: We analyzed all financial flows reported to the Organization for Economic Co-Operation and Development's Development Assistance Committee Creditor Reporting Service in 2010 to estimate these investments. We assessed the relationships between national stunting prevalence, stunting burden, under-5 mortality, and the amount of nutrition-specific and nutrition-sensitive ODA. Results: We estimate that, in 2010, a total of 379·4 million (M) US dollars (USD) was committed to nutrition-specific projects and programs of which 25 designated beneficiaries (countries and regions) accounted for nearly 85% (320 M). A total of 1.79 billion (B) was committed to nutrition-sensitive spending, of which the top 25 countries/regions accounted for 1.4 B (82%). Nine categories of development activities accounted for 75% of nutrition-sensitive spending, led by Reproductive Health Care (30·4%), Food Aid/Food Security Programs (14·1%), Emergency Food Aid (13·2%), and Basic Health Care (5·0%). Multivariate linear regression models indicate that the amount of nutrition-sensitive ( P = .001) and total nutrition ODA was significantly predicted by stunting prevalence ( P = .001). The size of the total population of stunted children significantly predicted the amount of nutrition-specific ODA ( P < .001). Conclusion: The recipient profile of nutrition-specific and nutrition-sensitive ODA is related but distinct. Nutrition indicators are associated with the level of nutrition-related ODA commitments to recipient countries. A reliable estimate of nutrition spending is critical for effective planning by both donors and recipients and key for success, as the global development community recommits to a new round of goals to address the interrelated causes of undernutrition in low-income countries.